Tumor-Infiltrating Lymphocytes, Crohn’s-Like Lymphoid Reaction, and Survival From Colorectal Cancer - Rozek, Laura S.; Schmit, Stephanie L.; Greenson, Joel K.; Tomsho, Lynn P.; Rennert, Hedy S.; Rennert, Gad; Gruber, Stephen B. (JNCI : Journal of the National Cancer Institute, 2016)
While clinical outcomes from colorectal cancer (CRC) are influenced by stage at diagnosis and treatment, mounting evidence suggests that an enhanced lymphocytic reaction to a tumor may also be an informative prognostic indicator. The roles of intratumoral T lymphocyte infiltration (TIL), peritumoral Crohn's-like lymphoid reaction (CLR), microsatellite instability (MSI), and clinicopathological characteristics in survival from CRC were examined using 2369 incident CRCs from a population-based case-control study in northern Israel. Cox proportional hazards regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for CRC-specific and all-cause mortality in multivariable models adjusted for age, sex, ethnicity, grade, stage, and MSI. All statistical tests were two-sided. Tumors with TIL/high-powered field (HPF) of 2 or greater were associated with a statistically significant increase in CRC-specific (P < .001) and overall survival (P < .001) compared with tumors with TIL/HPF of less than 2. Similarly, tumors with a prominent CLR experienced better CRC-specific (P < .001) and overall survival (P < .001) as compared with those with no response. High TILs (HR = 0.76, 95% CI = 0.64 to 0.89, P < .001) and a prominent CLR (HR = 0.71, 95% CI = 0.62 to 0.80, P < .001), but not MSI, were associated with a statistically significant reduction in all-cause mortality after adjustment for established prognostic factors. TILs and CLR are both prognostic indicators for CRC after adjusting for traditional prognostic indicators.